Polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) in urban soils of Glasgow, UK. (13th November 2018) - Kim, Alexander W.; Vane, Christopher H.; Moss-Hayes, Vicky L.; Beriro, Darren J.; Nathanail, C. Paul; Fordyce, Fiona M.; Everett, Paul A.
ABSTRACT: Concentrations of total organic carbon (TOC), total petroleum hydrocarbons, polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) were determined in 84 near-surface soils (5–20cm depth) taken from a 255km 2 area of Glasgow in the Clyde Basin, UK, during July 2011. Total petroleum hydrocarbon range was 79–2, 505mgkg –1 (mean 388mgkg –1 ; median 272mgkg –1 ) of which the aromatic fraction was 13–74 % (mean 44 %, median 43 %) and saturates were 28–87 % (mean 56 %, median 57 %). ∑ 16 PAH varied from 2–653mgkg –1 (mean 32.4mgkg –1 ; median 12.5mgkg –1 ) and ∑ 31 PAH range was 2.47–852mgkg –1 (mean 45.4mgkg –1 ; median 19.0mgkg –1 ). ∑PCB tri-hepta range was 2.2–1052μgkg –1 (mean 32.4μgkg –1 ; median 12.7μgkg –1 ) and the ∑PCB 7 range was 0.3–344μgkg –1 (mean 9.8μgkg –1 ; median 2.7μgkg –1 ). The concentration, distribution and source of the persistent organic pollutants were compared with those found in urban soils from other cities and to human health assessment criteria for chronic exposure to chemicals in soil. Total concentrations encountered were generally similar to other urban areas that had a similar industrial history. Benzo[ a ]pyrene concentrations were assessed against four different land use scenarios (irrespective of current land use) using generic assessment criteria resulting in six of 84 samples exceeding the residential criteria. Isomeric PAH ratios and relative abundance of perylene suggest multiple and environmentally modified pyrogenic PAH sources, inferred to be representative of diffuse pollution. ∑PCB 7 concentrations were exceeded in 10 % of sites using the Dutch target value of 20μgkg –1 . PCB congener profiles were environmentally attenuated and generally dominated by penta-, hexa- and hepta-chlorinated congeners.